MENINGKATKAN KEMAMPUAN MEMBACA AYAT PENDEK MELALUI METODE AL-BAYAN BAGI ANAK TUNAGRAHITA RINGAN KELAS IV DI SLB BASO KAB. AGAM - Azrina Oktavia (Universitas Negeri Padang, 2014)
Abstrack: The study begins with the problems that the authors found in class IV in SLB Baso, Kab. Agam, in learning to read children have problems seen when children read the first paragraph and the child stammered doubt that change the sound of reading the short paragraph. This research method was experiment research with single subject research (SSR) that used A-B design. Assessment in the study was measured by percentage Thus, it is evident that al-bayan method can improve the ability of students to read a short paragraph on mild mental retardation X Baso SLB class IV in the district. Agam. Kata kunci: Metode Al-Bayan; Kemampuan Membaca Ayat Pendek. Anak Tunagrahita Ringan